2011
DOI: 10.1111/j.1095-8649.2011.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antinutritional factors on plasma lipoprotein levels in Japanese flounder Paralichthys olivaceus

Abstract: This study examined the effects of four types of antinutritional factor (phytic acid, stachyose, soy saponins and soy isoflavones) on lipoprotein levels in plasma of Japanese flounder Paralichthys olivaceus. A basal diet was prepared with fish meal as primary protein source, the other diets were supplemented with 0·2, 0·4 or 0·8% phytic acid, 0·4, 0·8 or 1·5% stachyose, 0·1, 0·35 or 0·7% soy saponins and 0·10, 0·35 or 0·70% soy isoflavones, by dry mass, in place of white flour in the basal diet. Total choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
6
0
4
Order By: Relevance
“…A hypocholesterolaemic effect was reported in rainbow trout (Kaushik et al, ), gilthead seabream (Venou, Alexis, Fountoulaki, & Haralabous, ) and Atlantic cod (Hansen, Rosenlund, Karlsen, Koppe, & Hemre, ) fed a soy protein‐based diet. This phenomenon may be associated with a deficiency of cholesterol (Deng et al, ; Hossain, Focken, & Becker, ) or some anti‐nutritional factors such as saponin (Messina, ), phytosterol (Madani, Frenoux, Prost, & Belleville, ) or non‐starch polysaccharides (Deng et al, ) in SBM. In addition, studies found that cholesterol supplementation in the diet can enhance the growth performance and feed intake of channel catfish (Twibell & Wilson, ), rainbow trout (Deng, Bi, et al, ) and turbot (Yun et al, ; Yun, Mai, & Zhang, ) when the fish were fed high‐SBM diets.…”
Section: Introductionmentioning
confidence: 99%
“…A hypocholesterolaemic effect was reported in rainbow trout (Kaushik et al, ), gilthead seabream (Venou, Alexis, Fountoulaki, & Haralabous, ) and Atlantic cod (Hansen, Rosenlund, Karlsen, Koppe, & Hemre, ) fed a soy protein‐based diet. This phenomenon may be associated with a deficiency of cholesterol (Deng et al, ; Hossain, Focken, & Becker, ) or some anti‐nutritional factors such as saponin (Messina, ), phytosterol (Madani, Frenoux, Prost, & Belleville, ) or non‐starch polysaccharides (Deng et al, ) in SBM. In addition, studies found that cholesterol supplementation in the diet can enhance the growth performance and feed intake of channel catfish (Twibell & Wilson, ), rainbow trout (Deng, Bi, et al, ) and turbot (Yun et al, ; Yun, Mai, & Zhang, ) when the fish were fed high‐SBM diets.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the replacement of FM with SBM will greatly reduce the dietary cholesterol level. On the other hand, soya proteins and non-protein compounds present in SBM (such as soya saponins and phytosterol) reportedly lower the blood cholesterol level in fish ( 6 , 7 ) . Thus, the cholesterol-lowering action has already been reported in many fish species fed diets with SBM instead of FM ( 2 , 8 , 9 ) .…”
mentioning
confidence: 99%
“…This observation is in line with that of Bennetau‐Pelissero et al (), who reported that plasma cholesterol levels in males undergoing spermatogenesis were not affected by dietary genistein treatments in rainbow trout. However, a higher dietary supplementation with soy isoflavones markedly increased plasma cholesterol and triglyceride levels of Japanese flounder (Deng et al ). On the other hand, goldfish exposed to E2 (10 µg/g body weight) for a period of 5 mo also experienced elevations in plasma cholesterol and triacylglycerol concentrations (Sharpe and MacLatchy ).…”
Section: Discussionmentioning
confidence: 99%